Tidsstudie av containerhuggbil - Andersson, Robin (2011)
The fork lifter chipper truck is a concept which has been developed for harvest and transport of bio fuel. The system consists of one fork lifter chipper truck and 1, 2 or 3 transport lorries, usually two, which serves the fork lifter chipper truck. The system is driven by the fork lifter chipper truck that produces chipped material into a container on the truck. When the container has been filled the truck drives to the landing site where it’s offloaded. From the landing site the containers are being transported to industry by fork lifter trucks. The aim of the study was: - To measure the productivity of the system during various conditions considering distance of transportation, the quality of the windrow, mix of tree species and weight of the loads - To identify parameters within the system that could be improved - To compare the system to a similar system, tractor chipper and a truck equipped with a dipper Within the final thesis a time study has been carried out which have made it possible to estimate the productivity of the system and the time consumption of each work element. These data have then been used to analyze the system to show differences in productivity depending on different conditions on the site and constellation of vehicles. During the time study 50 % of the container chipper truck’s work time was consumed by chipping, which means that the utilization of the chipper is relatively low. The utilization of the chipper could be increased by reducing the distance between the windrow and the landing site, because the workelement container switch consumed 18 % of the worktime. Data were collected from SDC and Åkarewebben, which data showed that logging residues that have been extracted during summer and with a high share of pine had low moisture content when measured at industry. At the same time it was discovered that a dryer material took longer to chip because it was harder. During the time study of the system it was discovered that with a transport distance of 85 km one way, there were no waiting time when using one transport lorry. For two transport vehicles the optimal transport distance was 165 km one way. This means that at 85 km transport distance one transport vehicle should be used and at 165 km should two transport vehicles be used.